Sacraments of memory : Catholicism and slavery in contemporary African American literature - Salius, Erin Michael (Gainesville : University Press of Florida, 2018)
This book argues that Catholicism informs a major genre of African American literature in ways and with a significance that has gone largely unrecognized. Sacraments of Memory thus proposes a new framework for understanding the revisionist aims of these works, contextualizing the skepticism they exhibit towards historical realism in terms of a Catholic counter-tradition in American literature that has long been associated with superstition and irrationality.
Introduction: Towards a reading of the Catholic margin in contemporary narratives of slavery -- Toni Morrison's sacramental rememory -- A sacred communion: the Catholic side of possession in the autobiography of Miss Jane Pittman and Two wings to veil my face -- Catholicism and narrative time: transcending the past and the present in stigmata and oxherding tale -- Catholicism and narrative time, continued: divine prescience in Edward P. Jones's The Known World Coda.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 23, 2018).
Master record variable field(s) change: 072
Keywords: Slavery and the church -- Catholic Church; American literature -- African American authors -- History; Slavery in literature; Catholics in literature; African Americans in literature; LITERARY CRITICISM -- American -- General; African Americans in literature; American literature -- African American authors; Catholics in literature; Slavery and the church -- Catholic Church; Slavery in literature; LITERARY CRITICISM / American / African American; Electronic books; History